AB0013 Glomerular IL-4 Signaling Mediates Foot Process Effacement and Proteinuria in Nephrotic Syndromes. (15th July 2016) - Kim, A.H.; Akilesh, S.; Koziell, A.; Saunders, B.; Jain, S.; Hodgin, J.; Zinselmeyer, B.; Stappenback, T.; Miner, J.; Shaw, A.
Abstract : Background: Podocyte foot process effacement is a feature of proteinuria, thought to be a stereotyped response of the podocyte to injury. The stimulus for podocyte injury and foot process effacement is unknown, although changes in the actin cytoskeleton has been implicated. B cell depletion therapies have demonstrated efficacy in some patients with proteinuria including those with minimal change disease. Since pathogenic antibodies are not causative, we hypothesized that a B cell derived cytokine might be capable of directly inducing podocyte injury and foot process effacement. Objectives: Develop a B cell model of proteinuria in mice, and identify glomerulopathic cytokines derived from B cells. Methods: B cell model antigen model hen egg lysozyme (HEL) was biotinylated, complexed to avidin and injected into mice. HEL-specific B cells were adoptively transferred and proteinuria assessed. Two-photon microscopy was performed in vibrotomed kidneys following transfer of CFSE-labeled HEL-specific B cells with or without HEL antigen injection. Cultured podocyte membrane ruffling was assessed with DIC videomicroscopy. IL-4 expression in mice was achieved by hydrodynamically injecting murine IL-4 in the piggyBac vector system. Human kidney biopsies were assessed for phospho-STAT6 by immunohistochemistry. Results: We identified IL-4 as a B cell derived cytokine capable of stimulating podocyte actin rearrangement. Using a novel model of B cell induced proteinuria, B cells polarized to secrete IL-4 upon activation with HEL induced proteinuria without antibody or complement deposition. Using two-photon microscopy, we observed an accumulation of HEL-specific B cells within glomeruli containing HEL antigen. To confirm the glomerulopathic properties of IL-4, we overexpressed IL-4 in mice and found this was sufficient to induce foot process effacement and proteinuria. Inhibition of IL-4 signaling with a JAK1/3 inhibitor markedly reduced proteinuria in these IL-4 overexpressing mice. Finally, a subset of patients (31%) with steroid-sensitive nephrotic syndrome possessed glomerular STAT6 activation. Conclusions: These findings suggest a potential explanation for the utility of immunosuppression and more targeted anti-B cell therapy with rituximab in the treatment of steroid-sensitive nephrotic syndromes. These results support the role of IL-4 in human nephrotic syndromes and represents a novel therapeutic target. Disclosure of Interest: A. Kim Grant/research support from: Rheumatology Research Foundation, Kypha Inc., S. Akilesh: None declared, A. Koziell: None declared, B. Saunders: None declared, S. Jain Grant/research support from: NIDDK/NIH, J. Hodgin Grant/research support from: NephCure/American Society of Nephrology, B. Zinselmeyer: None declared, T. Stappenback: None declared, J. Miner Grant/research support from: NIDDK/NIH, A. Shaw Employee of: Genentech, Inc.